2007
DOI: 10.1016/j.ijpsycho.2007.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic characteristics of defensive hostility: Reactivity and recovery to active and passive stressors

Abstract: Defensive hostility has been attributed as an early risk factor of coronary heart disease.The autonomic characteristics of high defensive, high hostile (HD) and low defensive, high hostile (LD) men and women were assessed with a variety of cardiovascular (CV) measures. Reactivity and recovery to an active laboratory stressor (video game, VG) and a passive laboratory stressor (hand cold pressor, CP) of 15 HD men, 16 LD men, 16 HD women, and 16 LD women were recorded. It was predicted that the CV patterning asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 89 publications
1
21
0
2
Order By: Relevance
“…Our results are consistent with those obtained in previous studies, that is, that defensive hostile people obtain the highest values in the task phase (Brosschot, Gerin, & Thayer, 2006;Helmers, & Krantz, 1996;Jorgensen, & Thibodeau, 2006;Larson, & Langer, 1997;Shapiro, Goldstein, & Jamner, 1995;Vella, & Friedman, 2007). Moreover, we have found that this group of individuals takes longer to recover after a stress situation, that is, they score the highest values encountered during the recovery phase.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with those obtained in previous studies, that is, that defensive hostile people obtain the highest values in the task phase (Brosschot, Gerin, & Thayer, 2006;Helmers, & Krantz, 1996;Jorgensen, & Thibodeau, 2006;Larson, & Langer, 1997;Shapiro, Goldstein, & Jamner, 1995;Vella, & Friedman, 2007). Moreover, we have found that this group of individuals takes longer to recover after a stress situation, that is, they score the highest values encountered during the recovery phase.…”
Section: Discussionsupporting
confidence: 92%
“…In this way, nowadays, research has focused on defensive hostility (high hostility and high defensiveness) as one of the psychosocial factors with more weight and empirical support in its relationship with cardiovascular disease (Helmers, & Krantz, 1996;Jorgensen, & Thibodeau, 2006;Larson, & Langer, 1997;Vella, & Friedman, 2007). The trait of defensive hostility reflects an approach-avoid conflict between the desire for social approval and distrust of those who can provide such support (Jamner, Shapiro, Goldstein, & Hug, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…From the study on the classic Type A behavior pattern through the anger-hostility complex and hostility were conducted, in recent years, research has focused on the defensive hostility (high hostility and high defensiveness) as a risk factor in CVD (Guerrero & Palmero, 2010;Helmers & Krantz, 1996;Jamner, et al, 1991;Larson & Langer, 1997;Shapiro, et al, 1995;Palmero, et al, 2007;Vella & Friedman, 2007). The trait of defensive hostility reflects an approach-avoid conflict between the desire for social approval and distrust of those who www.intechopen.com Psychophysiological Cardiovascular Functioning in Hostile Defensive Women 467 can provide such support, and currently can be considered as one of the psychosocial factors with more weight and empirical support in its relationship with CVD.…”
Section: Psychosocial Risk Factors and Cardiovascular Diseasementioning
confidence: 99%
“…Geralmente é usada com a finalidade de coletar informações sobre como o indivíduo está reagindo ao tratamento analítico. Porém, com a evolução dos estudos, o conceito de níveis de defesa vem sendo empregado em outros focos de pesquisa que não de caráter psicológico ou psicanalítico (VELLA e FRIEDMAN, 2007;CICHOCKI, 2008;LÉVESQUE, MOSKOWITZ et al 2010;PORCERELLI et al, 2009;NELSON et al, 2009;RAMCHANDANI, 2006;PAREKH MA et al, 2010;SUKUL YR et al, 2009;PETRAGLIA J et al, 2009;ZANARINI MC et al, 2009;HYPHANTIS TN et al, 2008).…”
Section: Eu Posso Auto-observaçãounclassified